Design and Compartive Study of Overhead Tank Subjected to Seismic Forces in Different Zones (International Journal of Innovative Research in Computer Science & Technology, 2023)
Overhead tank are generally classified as  Ordinary Moment Resisting Frame (OMRF) and Special  Moment Resisting Frame (SMRF) supported response  reduction factor. Generally, the Overhead tank consists of  structural members like slabs, beams, columns, and footings, where the subjected loads are transferred between  the structural members and eventually transferred to the  Sub-grade of the soil. The behavior of the Overhead tank  is different for various sorts of loadings(Dead, Live, Wind, and Seismic) within the analysis and of overhead tank  usefully Indian standards codes suggest various loads  combinations supported probability of Occurrence. There  are around 52 load combinations and IS codes suggest the  lateral load (wind and seismic) acts independently but the  load governing the planning of structural members is to be  acknowledged. and therefore the present study to research  the consequences of wind and seismic forces on Overhead  tank structures of heights (15m) are considered in seismic  zones II, III, IV, V where length and width of the structures  are kept constant. An earthquake load is calculated as per  IS and wind pressure calculated as per IS 875-1987. The  analysis is done the use of STAAD.pro software.
Keywords: Overhead Tank; Seismic Forces; Earthquakes; Wind Pressure